110 Late gadolinium enhancement in primary degenerative mitral regurgitation predicts adverse right ventricular remodelling and exercise induced pulmonary hypertension. (5th June 2017) - Liu, Boyang; Edwards, Nicola; Bhabra, Moninder; Barker, Thomas; Patel, Ramesh; Steeds, Richard
Abstract : Introduction: The optimal timing of surgery in asymptomatic severe primary mitral regurgitation (MR) continues to be challenging. Late gadolinium enhancement (LGE) on cardiac magnetic resonance imaging (CMR) is an established imaging biomarker of irreversible myocardial fibrosis within the ventricles that is associated with worse prognosis in a broad range of cardiovascular diseases. There are limited data on the role of LGE in primary MR. Methods: Patients with moderate or severe primary degenerative MR were prospectively recruited for multiparametric cardiac MRI (1.5 Tesla scanner Magnetom Avanto, Siemens) and cardiopulmonary exercise stress echocardiography (Epic, Phillips). All patients were asymptomatic without a Class 1 indication for surgery. Patients with coronary artery disease or significant aortic valve disease were excluded. Results: LGE was present in 18 (30%) out of 61 patients (table 1). This was isolated to the point of insertion of the right ventricle (RV) into the septum in 8 cases. In the remaining 10 cases, LGE was located in the base of the left ventricle (LV; figure 1) or the papillary muscle heads. The presence of LGE was significantly associated with more severe MR, RV dilatation and reduced RV ejection fraction but no difference in LV size (LVEDV 92±22 ml/m 2 vs 99±23 ml/m2), mass (64±16g/m 2 vs 67±10 g/m 2 ) or function (LVEF 71±8% vs 69±6%) was found. Functionally, this translated to the presence of ventilation-perfusion mismatch (VE/VCO2), a measure of exercise induced pulmonary hypertension. There was no difference in the maximum exercise capacity of patients according to presence of LGE. Conclusion: We demonstrate LGE of the LV myocardium to be present in 30% of patients with asymptomatic moderate-severe primary degenerative MR, and represents an early marker of changes within the RV that are associated with adverse surgical outcomes and poorer prognosis following mitral valve surgery. Future studies are needed to confirm whether LGE is a new imaging biomarker that can be used to risk stratify severe asymptomatic MR patients for surgery.